2016
DOI: 10.1186/s12967-016-1074-7
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing in thyroid cancer

Abstract: Next-generation sequencing (NGS) in thyroid cancer allows for simultaneous high-throughput sequencing analysis of variable genetic alterations and provides a comprehensive understanding of tumor biology. In thyroid cancer, NGS offers diagnostic improvements for fine needle aspiration (FNA) cytology of thyroid with indeterminate features. It also contributes to patient management, providing risk stratification of patients based on the risk of malignancy. Furthermore, NGS has been adopted in cancer research. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 41 publications
0
41
0
2
Order By: Relevance
“…Next-generation sequencing (NGS) technology enables the simultaneous analysis of hundreds of genes of interest using targeted sequence panels. NGS has been used in molecular tumor classification, and the prediction of recurrence and metastasis in some human cancers (12). NGS data are also useful in patient's management, facilitating risk stratification of patients based on the risk of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing (NGS) technology enables the simultaneous analysis of hundreds of genes of interest using targeted sequence panels. NGS has been used in molecular tumor classification, and the prediction of recurrence and metastasis in some human cancers (12). NGS data are also useful in patient's management, facilitating risk stratification of patients based on the risk of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors identified a genetic alteration of the MAPK (Mitogen-Activating Protein Kinase) pathway in about 70% of PTC using NGS, detecting either point mutations or structural rearrangements [20]. This technique allowed the recognition of other novel molecular alteration in PTC, as in our case [21].…”
Section: Discussionmentioning
confidence: 73%
“…With the recent developments of genomic DNA testing, a sharpened picture of relevant gene alterations and molecular pathways can also be provided for thyroid malignancies. The availability of next-generation sequencing (NGS) approaches enables the large-scale analysis of cancer genotype from archived pathological material [10,11]. Several well-documented studies using NGS were performed to define the mutational spectrum of thyroid carcinoma, especially focusing on advanced and anaplastic carcinoma cohorts [12,13].…”
Section: Introductionmentioning
confidence: 99%